Pendampingan Dan Edukasi Pajak Kepada Guru SMKN 2 Tangerang - Agustine Dwianika; Fitriyah Nurhidayah (Empowerment: Jurnal Pengabdian Masyarakat, 2022)
Taxes are a part of all business fields, including BUMDes. This understanding is important for industry players, as well as their assistants. High school teachers are one of the BUMDes companions and also presenters in learning BUMDes Finance for students. So that the emphasis on the importance of culture as a determinant of the success of increasing tax compliance is very important. The Tax Center of Pembangunan Jaya University is one of the tax education activists that is highly committed to the effort to disseminate taxation widely. One of them is in the South Tangerang area. This study was conducted to find out how far the teachers of Vocational High School 2 South Tangerang, regarding the role of culture in BUMDes tax compliance. This study was conducted by comparing the knowledge of the role of culture before and after the teacher attended the training. Interviews were conducted to complete the results of the analysis and conclusions. The results showed that most of the participants experienced an increase in knowledge of the importance of the role of corruption culture in the success of efforts to increase BUMDes tax compliance